Degradation of polyvinyl chloride by a bacterial consortium enriched from the gut of Tenebrio molitor larvae - Xu, Ying; Xian, Zhuo-Ning; Yue, Wenlong; Yin, Chao-Fan; Zhou, Ning-Yi (Chemosphere (Oxford), 2023)
Polyvinyl chloride (PVC), a carbon backbone synthetic plastic containing chlorine element, is one of six widely used plastics accounting for 10% global plastics production. PVC wastes are recalcitrant to be broken down in the environment but release harmful chlorinated compounds, causing damage to the ecosystem. Although biodegradation represents a sustainable approach for PVC reduction, virtually no efficient bacterial degraders for additive-free PVC have been reported. In addition, PVC depolymerization by Tenebrio molitor larvae was suggested to be gut microbe-dependent, but to date no additive-free PVC degraders have been isolated from insect guts. In this study, a bacterial consortium designated EF1 was newly enriched from the gut of Tenebrio molitor larvae, which was capable of utilizing additive-free PVC for its growth with the PVC-mass reduction and dechlorination of PVC. PVC films inoculated with consortium EF1 for 30 d were analyzed by diverse polymer characterization methods including atomic force microscopy, scanning electron microscope, water contact angle, time-of-flight secondary ion mass spectrometry, Fourier transform infrared spectroscopy, differential scanning calorimetry, thermogravimetric analysis technique, and ion chromatography. It was found that bio-treated PVC films were covered with tight biofilms with increased –OH and –CC- groups and decreased chlorine contents, and erosions and cracks were present on their surfaces. Meanwhile, the hydrophilicity of bio-treated films increased, but their thermal stability declined. Furthermore, Mw, Mn and Mz values were reduced by 17.0%, 28.5% and 16.1% using gel permeation chromatography, respectively. In addition, three medium-chain aliphatic primary alcohols and their corresponding fatty acids were identified as PVC degradation intermediates by gas chromatography-mass spectrometry. Combing all above results, it is clear that consortium EF1 is capable of efficiently degrading PVC polymer, providing a unique example for PVC degradation by gut microbiota of insects and a feasibility for the removal of PVC wastes. [Display omitted] •A bacterial consortium was enriched from gut microbiota of Tenebrio molitor larvae.•The consortium utilized additive-free PVC as a sole carbon resource for its growth.•Various analyses showed an efficient biodegradation of PVC by the consortium.•Six intermediates of PVC biodegradation were identified by GC-MS.